THE EFFECT OF COMBINED ANTIHYPERTENSIVE THERAPY ON THE CONDITION OF THE ARTERIAL WALL IN WOMEN WITH ARTERIAL HYPERTENSION AND POSTMENOPAUSAL OSTEOPOROSIS - Bilovol, O.M.; Kniazkova, I.I.; Frolova, T.V.; Kuzminova, N.V.; Barbashova, V.O.; Starenkiy, V.P.; Bohun, M.V. (World of Medicine and Biology, 2022)
60 females (mean age 62.7±3.8 years) with arterial hypertension of stage II, degree 2, postmenopausal osteoporosis (according to the data of osteodensitometry) and not receiving regular antihypertensive therapy were examined. After baseline data registration hypertension therapy with a combination of lisinopril 10–20 mg and indapamide 2.5 mg per day was prescribed to 30 patients (group 1), and lisinopril 10–20 mg plus hydrochlorothiazide 12.5 mg per day for 12 weeks – to 30 patients (group 2). The control group consisted of 20 practically healthy females. All examined persons underwent clinical and laboratory examinations according to the protocols for the examination of patients with arterial hypertension and osteoporosis. Analysis of indicators after 12 weeks revealed the high antihypertensive efficacy of both treatment regimens. In patients with arterial hypertension and postmenopausal osteoporosis, according to the data of office measurement of blood pressure and daily monitoring of blood pressure, 12-week therapy with a combination of lisinopril and indapamide did not significantly differ from the therapy with lisinopril in combination with hydrochlorothiazide in terms of the severity of antihypertensive effect, an ability to normalize the daily profile of blood pressure and reduce pressure load indicators. Propagation velocity of pulse wave and central aortic pressure levels (cSBP and cPP) according to applanation tonometry significantly decreased more during 12-week therapy with lisinopril in combination with indapamide compared to the combination of lisinopril with hydrochlorothiazide, along with good tolerability in both treatment groups.